Edukasi dan Promosi dalam Industri Halal - Yuniarti, Desi; Hamzah, Nasir; Siradjuddin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
The inattention of the public as producers and consumers regarding the level of halal products is still a current phenomenon. This encourages the need for education and promotion regarding the importance of choosing halal products from various aspects. This research was carried out with the aim of formulating education and promotion of halal products based on strategy and substance. This research is research with a qualitative paradigm and also includes library research. Data sources come from online news, research results, and book literature. Based on this study, a synthesis was obtained that strategies for education and promotion of halal products can be carried out by promoting halal product research, integrating halal industry content in the educational curriculum, encouraging producers as subjects and objects of halal promotion and education, and choosing appropriate educational and promotional media. Education and promotion in the context of the halal industry must fulfill material and non-material substance.